Educational Strategies among Muslims in the Context of Globalization : Some National Case Studies - Daun, Holger; Walford, Geoffrey (Brill Book Archive Part 1, ISBN: 9789004472495., 2004)
This volume deals with Islamic conceptualization of knowledge, various types of Islamic education; and educational strategies among selected groups of Muslims in Islamized countries (Pakistan, Iran, Morocco, Senegal, and so on) as well as countries in Europe where Muslims form important minorities. The first chapter gives an overview of Islamic educational arrangements in the context of globalization and chapter two presents some principal ideological orientations among Muslims. The remaining chapters describe educational arrangements available to Muslim parents in different countries. The book is useful as a textbook in social sciences courses, teacher training institutions and among the general public.